Cyclohexamer [-(d-Phe-azaPhe-Ala)2-]: good candidate to formulate supramolecular organogels. Issue 71 (7th December 2020) - Ibrahim, Mohamed I. A.; Pickaert, Guillaume; Stefan, Loïc; Jamart-Grégoire, Brigitte; Bodiguel, Jacques; Averlant-Petit, Marie-Christine
Abstract : Molecular self-assembly is a fascinating process which has become an area of great interest in supramolecular chemistry, as it leads in certain cases to molecular gels. Abstract : Molecular self-assembly is a fascinating process which has become an area of great interest in supramolecular chemistry, as it leads in certain cases to molecular gels. Organogels formulated from low molecular weight compounds (LMWOGs) have attracted much interest in the past decades due to their applications as new soft materials. Herein, we report on the ability of the cyclic pseudopeptide cyclo-[-(d -Phe-azaPhe-Ala)2 -] (2 ) to self-assemble in some aromatic solvents and to form organogels driven by non-covalent forces, mainly hydrogen bonding and π-stacking interactions. Comprehensive FTIR and NMR studies emphasized that this cyclic aza-peptide adopts a β-turn conformation at low concentration in toluene, while an equilibrium between the monomeric states (intramolecular forces) and the supramolecular structures (intra- and intermolecular forces) is established at high concentration (gel state). Rheological investigations of the organogels highlight the dependence of their stiffness (up to ∼4 kPa) and sol/gel transition temperatures (up to 100 °C) as a function of the solvent and concentration of gelator used. The formulation of fibrous structures confirmed the phenomenon of self-assembly. Finally, we found that cyclo-[-(d -Phe-azaPhe-Ala)2 -] is an effective organogelator for application in phase selective gelation (PSG) of organic solvents from aqueous/organic mixtures with recovery percents up to 96%.